COPD-Type lung inflammation promotes K-ras mutant lung cancer through epithelial HIF-1α mediated tumor angiogenesis and proliferation - De la Garza, Maria Miguelina (Oncotarget, 2018)
Chronic obstructive pulmonary disease (COPD), an inflammatory disease of the lung, is an independent risk factor for lung cancer. Lung tissues obtained from human smokers with COPD and lung cancer demonstrate hypoxia and up-regulated hypoxia inducible factor-1 (HIF-1). HIF-1 activation is the central mechanism for controlling the cellular response to hypoxia during inflammation and tumor development. These facts suggest a link between COPD-related airway inflammation, HIF-1, and lung cancer. We have previously established a mouse model of COPD-like airway inflammation that promotes lung cancer in a K-ras mutant mouse model (CC-LR). Here we show that tumors in the CC-LR model have significantly elevated levels of HIF-1α and HIF-1 activity. To determine the tumor-promoting functions of HIF-1 in CC-LR mice, the gene Hif1a which encodes HIF-1α and is required for HIF-1 activity, was disrupted in the lung epithelium of CC-LR animals. Airway epithelial specific HIF-1α deficient mice demonstrated significant reductions in lung surface tumor numbers, tumor angiogenesis, and tumor cell proliferation in the absence or presence of COPD-like airway inflammation. In addition, when CC-LR mice were bred with transgenic animals that overexpress a constitutively active mutant form of human HIF-1α in the airway epithelium, both COPD- and adenocarcinoma-like phenotypes were observed. HIF-1α overexpressing CC-LR mice had significant emphysema, and they also showed potentiated tumorigenesis, angiogenesis, and cell proliferation accompanied by an invasive metastatic phenotype. Our gain and loss of function studies support a key role for HIF-1α in the promotion of lung cancer by COPD-like inflammation.